2020
DOI: 10.6018/eglobal.420681
|View full text |Cite
|
Sign up to set email alerts
|

Medición de la calidad de vida en adultos mayores institucionalizados de Lima (Perú)

Abstract: Introducción: Los adultos mayores experimentan cambios a nivel físico, cognitivo, social y emocional que tienen un impacto en su calidad de vida. Por lo tanto, resulta necesario disponer de instrumentos con adecuadas propiedades de medición para identificar y medir esta variable, de modo que las inferencias o interpretaciones sean válidas para la toma de decisiones. Objetivo: El objetivo del estudio fue analizar las propiedades de medición del cuestionario de calidad de vida WHOQOL-OLD en adultos mayores perua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
1
2
1
5
Order By: Relevance
“…Our findings on the dimensions of quality of life in older adults of both countries were consistent with previous studies carried out in other Latin-American countries such as Brazil [ 74 ], Chile [ 68 ], Peru [ 42 , 75 ], and Mexico itself [ 41 ]. Specifically, the levels of quality of life of the Mexican older adults reported in our study are similar to those shown by González-Celis and Gómez-Benito [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings on the dimensions of quality of life in older adults of both countries were consistent with previous studies carried out in other Latin-American countries such as Brazil [ 74 ], Chile [ 68 ], Peru [ 42 , 75 ], and Mexico itself [ 41 ]. Specifically, the levels of quality of life of the Mexican older adults reported in our study are similar to those shown by González-Celis and Gómez-Benito [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, the levels of quality of life of the Mexican older adults reported in our study are similar to those shown by González-Celis and Gómez-Benito [ 41 ]. On the other hand, the perception of quality of life indicated by the Ecuadorian and Mexican older adults participating in our study was higher than the results obtained by Urzúa and Navarrete in Chile [ 68 ] and Queirolo et al [ 42 ] and Hernandez-Huayta et al [ 75 ] in Peru.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…(9,10) Therefore, older adults are an important issue in which a priority challenge is represented for health authorities and health professionals, whose function is to provide a better quality of life for successful aging. (11,12,13) A study conducted in Poland found that people aged 60 to 80, almost 30 % suffer from at least a moderate level of disability and more than 10 % experience severe disability. However, the dominant age group studied were people between 60 and 80 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, en el enfoque del envejecimiento, el Tercer Plan Nacional de Derechos Humanos [7, p. 59] elaboró un plan de Derechos que se incorporó a la población adulta mayor como grupo de especial protección, proponiendo acciones estratégicas que contribuyan a cumplir con las políticas públicas diseñadas por el Estado, y con ello, estudios como "Medición de la calidad de vida en adultos mayores institucionalizado de Lima" [8], el "Nivel de dependencia y la percepción de la calidad de vida de los adultos mayores del centro de atención residencial geriátrico San Vicente de Paúl" [9], el "Calidad de vida y estrategias de afrontamiento en adultos mayores de Lima Metropolitana" [10], entre otros; muestran cómo la aplicación del Módulo WHOQOL-OLD arroja resultados que pueden ser considerados para obtener información sobre la Calidad de Vida del adulto mayor, siendo importante por ello, validar dicho instrumento.…”
Section: Introductionunclassified